2017
DOI: 10.1073/pnas.1706689114
|View full text |Cite
|
Sign up to set email alerts
|

Detection of immune responses after immunotherapy in glioblastoma using PET and MRI

Abstract: Contrast-enhanced MRI is typically used to follow treatment response and progression in patients with glioblastoma (GBM). However, differentiating tumor progression from pseudoprogression remains a clinical dilemma largely unmitigated by current advances in imaging techniques. Noninvasive imaging techniques capable of distinguishing these two conditions could play an important role in the clinical management of patients with GBM and other brain malignancies. We hypothesized that PET probes for deoxycytidine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 33 publications
2
67
0
Order By: Relevance
“…In the orthotopic Gl261 model the combination of i.v. contrast MRI and [ 18 F]-2-fluoro-d-(arabinofuranosyl) cytosine PET/CT enabled the distinction of regions of high immune inflammatory activity/infiltration in animals treated with DC vaccine and/or anti-programmed cell death-1 mAb (27), closing the gap between preclinical models and clinical treatment/monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In the orthotopic Gl261 model the combination of i.v. contrast MRI and [ 18 F]-2-fluoro-d-(arabinofuranosyl) cytosine PET/CT enabled the distinction of regions of high immune inflammatory activity/infiltration in animals treated with DC vaccine and/or anti-programmed cell death-1 mAb (27), closing the gap between preclinical models and clinical treatment/monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Other PET probes are also under investigation. A recent study demonstrated the feasibility of PET probes targeting deoxycytidine kinase to evaluate immune cell aggregation in gliomas [48]. While this technique requires further evaluation in a clinical setting, amino acid PET is currently available to patients and has shown the ability to differentiate between pseudoprogression and GBM recurrence [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a radiolabeled [ 89 Zr]IAB22M2C has the potential to visualize CD8 + T-cell-enriched tumor tissue [168]. The assessment of immune cells infiltrating tumors has also been investigated with PET using radiolabeled clofarabine (2-chloro-2 -deoxy-2 -[ 18 F]fluoro-9-b-D-arabinofuranosyl-adenine; [ 18 F]CFA) [169]. [ 18 F]CFA is a substrate for the enzyme deoxy-cytidine kinase, which is overexpressed in immune cells such as CD8 + T-cells [169].…”
Section: Immuno-imaging: Immuno-pet and Imaging Of T-cellsmentioning
confidence: 99%